Cardiac Cx43 and ECM Responses to Altered Thyroid Status Are Blunted in Spontaneously Hypertensive versus Normotensive Rats - Sykora, Matus; Szeiffova Bacova, Barbara; Egan Benova, Tamara; Barancik, Miroslav; Zurmanova, Jitka; Rauchova, Hana; Weismann, Peter; Pavelka, Stanislav; Kurahara, Lin Hai; Slezak, Jan; Soukup, Tomas; Tribulova, Narcis (International journal of molecular sciences, 2019)
Heart function and its susceptibility to arrhythmias are modulated by thyroid hormones (THs) but the responsiveness of hypertensive individuals to thyroid dysfunction is elusive. We aimed to explore the effect of altered thyroid status on crucial factors affecting synchronized heart function, i.e., connexin-43 (Cx43) and extracellular matrix proteins (ECM), in spontaneously hypertensive rats (SHRs) compared to normotensive Wistar Kyoto rats (WKRs). Basal levels of circulating THs were similar in both strains. Hyperthyroid state (HT) was induced by injection of T3 (0.15 mg/kg b.w. for eight weeks) and hypothyroid state (HY) by the administration of methimazol (0.05% for eight weeks). The possible benefit of omega-3 polyunsaturated fatty acids (Omacor, 200 mg/kg for eight weeks) intake was examined as well. Reduced levels of Cx43 in SHRs were unaffected by alterations in THs, unlike WKRs, in which levels of Cx43 and its phosphorylated form at serine368 were decreased in the HT state and increased in the HY state. This specific Cx43 phosphorylation, attributed to enhanced protein kinase C-epsilon signaling, was also increased in HY SHRs. Altered thyroid status did not show significant differences in markers of ECM or collagen deposition in SHRs. WKRs exhibited a decrease in levels of profibrotic transforming growth factor β1 and SMAD2/3 in HT and an increase in HY, along with enhanced interstitial collagen. Short-term intake of omega-3 polyunsaturated fatty acids did not affect any targeted proteins significantly. Key findings suggest that myocardial Cx43 and ECM responses to altered thyroid status are blunted in SHRs compared to WKRs. However, enhanced phosphorylation of Cx43 at serine368 in hypothyroid SHRs might be associated with preservation of intercellular coupling and alleviation of the propensity of the heart to malignant arrhythmias.
Keywords: Extracellular Matrix Proteins; potkani inbrední WKY; Male; hypertenze; Thyroid Hormones; hormony štítné žlázy; potkani inbrední SHR; Myocardium; mužské pohlaví; Hypertension; extracelulární matrix - proteiny; heart; Animals; connexin-43; zvířata; spontaneously hypertensive rats; Rats, Inbred SHR; konexin 43; Connexin 43; extracellular matrix; Rats, Inbred WKY; myokard; thyroid hormones